Akselerasi Pelatihan Manajemen Sumber Daya Industri: Pengelolaan Produk - Miran, Ikas; Rahman, Sarli; Fadrul, Fadrul; Aprila, Bord Nandre; Setyawan, Onny (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
Industrial resource management training is an important aspect in increasing the operational efficiency and effectiveness of an industry. This training acceleration aims to accelerate the mastery of skills and knowledge needed in managing industrial products. This program is designed to provide an in-depth understanding of product management strategies, including planning, development, production, distribution and marketing. With structured and intensive training methods, it is hoped that participants will be able to apply industrial resource management concepts effectively in the work environment. The results of this accelerated training are expected to improve overall organizational performance, create high quality products, and strengthen competitiveness in the market. Case studies and practical simulations are used to ensure that participants not only understand the theory, but are also able to apply it in real situations. Keywords: Acceleration, training, resources, industry, product management